Assessing the impact of a shadowing programme on in-hospital mortality following trainee doctors' changeover - Balinskaite Violeta; Bottle Alex; Aylin Paul (BMC, 2021)
Abstract Background To assess the impact on seven-day in-hospital mortality following the introduction in 2012 of a shadowing programme for new UK medical graduates requiring them to observe the doctor they are replacing for at least 4 days before starting work. Methods Data on emergency admissions were derived from Hospital Episode Statistics between 2003 and 2019. A generalised estimating equation model was used to examine whether the introduction of the programme was associated with a change in mortality. Results There were 644,018 emergency admissions, of which 1.8% (7612) ended in death in hospital within a week following the admission. Throughout the study period, there was an annual increase in the number of emergency admissions during July and August, though in-hospital mortality rates declined. The generalised estimating equation analysis found no significant change in the odds of death within 7 days after admission for patients admitted on the first Wednesday in August compared with patients admitted on the last Wednesday in July (OR = 1.03, 95% CI 0.94-1.13, p = 0.53). Furthermore, there was no significant change observed for any clinical diagnosis category following the introduction of the shadowing programme. Conclusion There was a rising trend in the number of emergency admissions over the study period, though mortality was decreasing. We found no significant association between the introduction of shadowing programme and in-hospital mortality; however, lack of power means that we cannot rule out a small effect on mortality. There are other outcomes that might have changed but were not examined in this study.